Pengembangan keterampilan organisasi, komunikasi, kerjasama, dan etika melalui pelatihan badan eksekutif mahasiswa - Fridayani, Januari Ayu (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2024)
Higher education is not only responsible for the processes of education and research, but also for developing student leadership through Student Executive Boards (BEM). A comprehensive BEM training program can prepare students to play important roles within organizations, develop managerial skills, communication, teamwork, and ethical principles. This study aims to investigate the effectiveness of BEM training sessions in developing organizational, communication, teamwork, and ethical skills at the Faculty of Theology, Sanata Dharma University. The training sessions consist of two main sessions. The first session, covering the basics of organization, structure, and responsibilities of BEM, provides students with a deep understanding of organizational governance and the tasks carried out by BEM executives. The second session, focusing on managing communication, teamwork, and ethics, enhances students' skills in effective communication, teamwork, and adherence to ethical principles in BEM activities. BEM training at the Faculty of Theology, Sanata Dharma University, has proven its strategic value in developing student leadership. By strengthening organizational, communication, teamwork, and ethical skills, students involved in BEM can become competent and responsible leaders in the future. This article demonstrates the efficacy of this technique in equipping students to engage in organizational activities. Following the course, students successfully reorganized the BEM organization, enhancing clarity in the roles of each member and effectively resolving internal issues through the use of learned communication strategies. Furthermore, the training facilitated BEM in enhancing their ability to effectively organize yearly events and promote transparency in decision-making. This had a positive impact on both the campus community and the broader community.